Expression Profile of Genes Associated with the Proteins Degradation Pathways in Colorectal adenocarcinoma - Martyna, Bednarczyk; Małgorzata, Muc-Wierzgoń; Nikola, Zmarzły; Beniamin, Grabarek; Urszula, Mazurek; Grażyna, Janikowska (Current pharmaceutical biotechnology, 2019)
Changes in expression of genes associated with proteins or organelles degradation system in the cell may be a cause or signal to carcinogenesis. Thus, the aim of this study was to assess the profile of gene expression linked to the degradation systems of proteins or organelles in histo-pathologically confirmed colorectal adenocarcinoma in relation to normal colon tissue. Using oligonucleotide microarrays and GeneSpring 13.0, and PANTHER 13.1 software's we characterized 1095 mRNAs linked to the degradation system of proteins and organelles in sections of colorectal cancer from patients at various clinical stages of disease. Subsequent analyses with restrictive assumptions narrowed down the number of genes differentiating cancer, assuming a P-value of less than 0.05. We found that most of the significant genes were silenced in the development of colorectal cancer. The FOXO1 had the lowest fold change value in the first clinical stage (CSI) comparing to the control. The HSPA8 was up-regulated in the two early clinical stages (CSI and CSII), and UBB only in the CSI. Only little-known PTPN22 showed increasing expression at all stages. In summary, the examined colorectal adenocarcinoma samples were characterized by almost complete silencing of the significant genes associated with the degradation of proteins and mitochondria in transcriptomic level. The FOXO1, HSPA8 and UBB genes may become potential diagnostic and/or therapeutic targets in the early stage of this cancer.